Numerical investigation of roof heating impacts on thermal comfort and air quality in urban canyons - Ghobadi, Parisa; Hosseini, Seyyed Hossein; Ahmadi, Toran; Calautit, John Kaiser (Elsevier, 2017)
Impacts of thermal and buoyancy forces on the thermal comfort and air quality in urban canyons with different H/W ratios and rise/run ratio of rooftops are studied. 18 isothermal and non-isothermal models are studied by CFD modeling validated with experimental data from the literature. Based on the results, thermal buoyancy is observed to be effective in improving human comfort in the urban canyon. The temperature difference between roof surface and air increases the speed of air and contaminant transport in urban canyons. While the increase in height and tilt of structures around urban areas have shown to reduce thermal buoyancy. In broad canyons such as H/W = 0.5, an increase in height and slope of the roof causes the thermal comfort of leeward, windward, and central regions to move away from the neutral comfort conditions. In regular canyons, H/W = 1, the thermal comfort reduces for highly slanted roofs models. Domed roof leads to the lack of thermal comfort in upper levels of passages in leeward, windward, and central regions. In deep canyons, H/W = 2, high level of thermal comfort appears only for flat roofs. With an increase in roof height (rise/run), Predicted Mean Vote PMV index moves away from the comfort range. By increasing H/W ratio, roof height, wind comfort, and air quality inside regular and deep urban canyons, it was observed that the thermal buoyancy force leads to the reduction in thermal comfort.